Impact of mitral regurgitation on cardiovascular hospitalization and death in newly diagnosed heart failure patients. (29th May 2020) - Cork, David P.; McCullough, Peter A.; Mehta, Hirsch S.; Barker, Colin M.; Gunnarsson, Candace; Ryan, Michael P.; Baker, Erin R.; Van Houten, Joanna; Mollenkopf, Sarah; Verta, Patrick
Abstract: Aims: Heart failure (HF) carries a poor prognosis, and the impact of concomitant mitral regurgitation (MR) is not well understood. This analysis aimed to estimate the incremental effect of MR in patients newly diagnosed with HF. Methods and results: Data from the IBM® MarketScan® Research Databases were analysed. Included patients had at least one inpatient or two outpatient HF claims. A 6 month post‐period after HF index was used to capture MR diagnosis and severity. HF patients were separated into three cohorts: without MR (no MR), not clinically significant MR (nsMR), and significant MR (sMR). Time‐to‐event analyses were modelled to estimate the clinical burden of disease. The primary outcome was a composite endpoint of death or cardiovascular (CV)‐related admission. Secondary outcomes were death and CV hospitalization alone. All models controlled for baseline demographics and co‐morbidities. Patients with sMR were at significantly higher risk of either death or CV admission compared with patients with no MR [hazard ratio (HR) 1.26; 95% confidence interval (CI) 1.15–1.39]. When evaluating death alone, patients with sMR had significantly higher risk of death (HR 1.24; 95% CI 1.08–1.43) compared with patients with no MR. When evaluating CV admission alone, patients with MR were at higher risk of hospital admission vs. patients with no MR, and the magnitude was dependent upon the MR severity: sMR (HR 1.55; 95% CI 1.38–1.74) and nsMR (HR 1.23; 95% CI 1.08–1.40). Conclusions: Evidence of MR in retrospective claims significantly increases the clinical burden of incident HF patients. Time to death and CV hospitalizations are increased when MR is clinically significant.